2015
DOI: 10.1371/journal.pone.0120869
|View full text |Cite
|
Sign up to set email alerts
|

Dicarbonyl L-Xylulose Reductase (DCXR), a “Moonlighting Protein” in the Bovine Epididymis

Abstract: During maturation and the acquisition of their fertilization potential, male germ cells are subjected to various sequential modifications that occur in the epididymis. Protein addition, reorganization or withdrawal, comprise some of these modifications. Dicarbonyl L-xylulose reductase (DCXR), a multifunctional protein involved in various enzymatic and protein interaction processes in different physiological systems, is one of the proteins added to spermatozoa in the epididymis. DCXR is a well-conserved protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…The mechanisms by which OGT is lost from sperm during epididymal transit is still unknown. Most reports indicate that proteins are incorporated to sperm during maturation (reviewed in Gervasi and Visconti, 2017 ), however the protein dicarbonyl L-xylulose reductase (DCXR) has been reported to be selectively removed from bovine sperm during maturation (Akintayo et al, 2015 ). Our data suggest that OGT is lost from the sperm flagellum during transit through the epididymis, and further investigations are necessary to determine whether it is due to the specific degradation of this transferase.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which OGT is lost from sperm during epididymal transit is still unknown. Most reports indicate that proteins are incorporated to sperm during maturation (reviewed in Gervasi and Visconti, 2017 ), however the protein dicarbonyl L-xylulose reductase (DCXR) has been reported to be selectively removed from bovine sperm during maturation (Akintayo et al, 2015 ). Our data suggest that OGT is lost from the sperm flagellum during transit through the epididymis, and further investigations are necessary to determine whether it is due to the specific degradation of this transferase.…”
Section: Discussionmentioning
confidence: 99%
“…The epididymis was an important reproductive organ that is responsible for transmission, concentration, and storage of sperm in male mammals. , Spermatozoa attain fertilization ability after undergoing a series of structural and functional alterations in the epididymis. ,, Therefore, we first observed the morphological features of the epididymal luminal epithelial cells after fluoride exposure. The results of the current study revealed that fluoride exposure led to the loss of nuclei in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, proteomic profiling of frozen–thawed human spermatozoa [ 101 ] unraveled a significant upregulation of several proteins including clusterin (CLU) as a major sperm glycoprotein [ 133 ], tektin (TEKT) 2 and 3 present in the axoneme and periaxonemal structures necessary for progressive motility of spermatozoa [ 134 ], and L-xylulose reductase (DCXR), a multifunctional protein involved in various enzymatic and protein interaction processes [ 135 ]. On the other hand, proteins such as acrosin (ACR), the major proteinase present in the acrosome of mature spermatozoa [ 136 ], calmodulin (CALM1) involved in calcium signal transduction pathways [ 137 ], cytochrome (CYC2), and NADH-cytochrome b5 reductase2 (CYB5R2) as critical elements involved in sperm mitochondrial biogenesis and metabolism [ 138 , 139 ] were significantly decreased following cryopreservation, resulting in reduced post-thaw semen quality.…”
Section: Protein Markersmentioning
confidence: 99%